2000
DOI: 10.1080/713803591
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Two cDNAs Encoding Sulfatases in the Roman Snail, Helix pomatia

Abstract: SummaryThe sulfatase from the snail Helix pomatia is widely used for analytical applications. We have investigated the content of sulfatases in H. pomatia, using a biochemical and a molecular approach. A 112-kDa protein from the intestinal juice of H. pomatia comigrated with sulfatase activity when chromatographed on Sephacryl S300 and concanavalin A-Sepharose. The N-terminal amino acid sequence of the protein was similar to one of three sulfatase motifs de ned by sequence alignment of known sulfatases. Degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…ROPN1 (ropporin 1), a protein kinase A-like (R2D2) protein, is associated with cAMP dependent protein kinase (PKA)/A-kinase anchoring protein (AKAP). Fujita et al reported that ROPN1 is localized to the sperm flagella (Fujita et al, 2000). Another study reported decreased expression of ROPN1 in the spermatozoa of patients with low sperm motility (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…ROPN1 (ropporin 1), a protein kinase A-like (R2D2) protein, is associated with cAMP dependent protein kinase (PKA)/A-kinase anchoring protein (AKAP). Fujita et al reported that ROPN1 is localized to the sperm flagella (Fujita et al, 2000). Another study reported decreased expression of ROPN1 in the spermatozoa of patients with low sperm motility (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This catalytic region of SULF1 and SULF2 display 80% identity. A post-translationally modified cysteine forms a C-formylglycine within the active sites of both enzymes[18] that is involved in hydrolytic cleavage of sulfates from the 6-O position of glucosamines in substrates[19-24]. Theoretical models of the catalytic cores of SULF1 and SULF2 can be built using 13 homologous crystallographic structures at present.…”
Section: Sulf1 and Sulf2 Domain Structure Substrate Specificity And mentioning
confidence: 99%
“…Sulfatases are highly proficient enzymes, with catalytic proficiencies (( k cat / K M )/ k uncat ) well above 1 × 10 13 to 1 × 10 17 M –1 for the model substrate 4-nitrophenyl sulfate 1d (Scheme ). − Despite their occurrence in eukaryotes and prokaryotes, relevance for a variety of key processes (e.g., development, − germination, resistance against toxic defense molecules, , mucin desulfatation, − or degradation of mucopolysaccharides , ) and the danger of various diseases as a result of their malfunction (e.g., lysosomal disorders , ), their mechanism has not been studied in the same detail as that of the related phosphatases.…”
mentioning
confidence: 99%